The Effectiveness of Frontloading Strategies to Improve Students’ Reading Comprehension based on Gender - Ahmad Ad Dairaby (CV. Tripe Konsultan, 2023)
This research belongs to quantitative research and aims to find the effectiveness of the frontloading strategy to improve students’ reading comprehension based on gender. The instrument given to the students was reading comprehension in the context of a narrative text. The research subject consisted of 25 students. This research only used experimental class for this research. As a result of this research, there was a significant improvement between pre-test and post-test scores. The result obtained from the sample T-test was found that the p-value (0,000) was lower than 0.05, and the t-observed (4,337) was higher than the t-table (2.059). While the result of differences in scores between females and a male based on post-test, the p-value (.240) was higher than 0.05, there were no significant differences in reading comprehension scores between females and males. So, this strategy makes students interested in teaching and learning reading comprehension. This technique also helps students to understand about material easily.